Sistem Informasi Pendaftaran Anggota Baru Pada Palang Merah Indonesia (PMI) Jakarta - Endah Wiji Lestari (Paradigma, 2019)
Palang Merah Indonesia is a humanitarian organization with legal status, Palang Merah Indonesia that will be discussed in this study is the Palang Merah Indonesia South Jakarta. The New Member Registration System at the Palang Merah Indonesia South Jakarta is currently using a conventional system, which still uses paper media in the recording of new members, making reports and even making members' cards, in the process of searching for data administrative members also experience difficulties, where frequent data loss or data that is already dull. So it becomes a problem in the organization. Therefore, in this study, the authors propose to create a desktop-based new member registration management information system that is expected to help the process of managing data in the organization. In this writing, the author uses the Waterfall Method for the development of the system by analyzing, doing the design phase, coding, and testing the program.